Ocorrência de Plasmodium spp. e Haemoproteus spp. em aves aquáticas migratórias (Rynchops niger e Phaetusa simplex ) na Reserva de Desenvolvimento Sustentável Mamirauá, Médio Solimões, Amazonas, Brasil - Fernanda Lopes Roos (2014)
Many studies conducted worldwide have demonstrated both prevalence and occurrence of avian hemoparasites in several vertebrate hosts. However, little is known about the occurrence of hemoparasites such as Plasmodium spp. and Haemoproteus spp. in the Brazilian Amazon. The region of the Medium Solimões river, in the Amazonas state, is an area of reproduction and nesting of a variety of species of migratory aquatic birds such as Rynchops niger, Sternula superciliaris and Phaetusa simplex, which form reproductive mixed colonies with high population densities. These migratory birds parasitized by hemoparasites may represent a potential source of infection to other susceptible birds of the different regions of Brazil and America due to the large range of the migration routes of these animals. This study aimed to determine the prevalence and diversity of species and/or lineages of Plasmodium and Haemoproteus in the R. niger and P. simplex species in the Reserve of Sustainable Development Mamirauá, Médio Solimões, Amazon, Brazil based on the microscopic observation of blood smears and sequencing of the cytochrome b mitochondrial gene. A total of 173 birds were captured. From the blood smears analysis was observed an occurence of 17,34% of infected birds by Plasmodium/Haemoproteus. In the molecular analysis 6,36% of birds were positives. The combination of microscopy with PCR identified 30 positive samples (17,34%). Six sequences were obtained being three different lineages identified, two of Plasmodium and one of Haemoproteus. The Haemproteus lineage described and detected in four adults of species R. niger in Mamirauá has 100% sequence compatible with Haemoproteus macrovacuolatus described in a anseriforme in Colombia. Considering that parasites diseases, such as the avian malaria, could be responsible for a significant number of extinctions of wild species, so the evaluation of these parameters becomes an important tool in the diagnosis of environmental health and for the development of programs for the management of natural resources and biodiversity conservation in tropical areas.